Classification of stationary neuronal activity according to its information rate - Kostal, Lubomir; Lánský, Petr (Network (Bristol, England), 2006)
We propose a measure of the information rate of a single stationary neuronal activity with respect to the state of null information. The measure is based on the Kullback-Leibler distance between two interspike interval distributions. The selected activity is compared with the Poisson model with the same mean firing frequency. We show that the approach is related to the notion of specific information and that the method allows us to judge the relative encoding efficiency. Two classes of neuronal activity models are classified according to their information rate: the renewal process models and the first-order Markov chain models. It has been proven that information can be transmitted changing neither the spike rate nor the coefficient of variation and that the increase in serial correlation does not necessarily increase the information gain. We employ the simple, but powerful, Vasicek's estimator of differential entropy to illustrate an application on the experimental data coming from olfactory sensory neurons of rats.
Keywords: modely neurologické; počítačové zpracování signálu; entropie; nervové dráhy; časové faktory; Time Factors; Signal Processing, Computer-Assisted; Markov Chains; Animals; Markovovy řetězce; akční potenciály; Action Potentials; Entropy; Models, Neurological; Neural Pathways; neurony; zvířata; Neurons